Nonwoven fabric and clothing
The nonwoven fabric, composed of specifically engineered polyester or polyamide fibers and a water repellent agent, addresses the challenges of breathability, strength, and recyclability in waterproof and breathable materials, achieving enhanced performance and recyclability.
Patent Information
- Application Number
- JP2024164741
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2023-09-28
- Filing Date
- 2024-09-24
- Publication Date
- 2025-04-09
AI Technical Summary
Existing waterproof and breathable materials face challenges such as low breathability, insufficient water vapor release, low fiber strength, and difficulty in producing monomaterials made of polyester or polyamide using electrospinning due to solubility issues.
A nonwoven fabric primarily composed of polyester or polyamide fibers with specific pore diameter distributions, fiber diameter variations, and the inclusion of a water repellent agent, which enhances water resistance, breathability, and strength while being recyclable.
The nonwoven fabric achieves high water resistance, breathability, and strength, making it suitable for waterproof and breathable applications while being easily recyclable, thus addressing the limitations of existing technologies.
Smart Images

Figure 2025059017000002 
Figure 2025059017000001
Abstract
Description
[Technical field]
[0001] The present invention relates to a nonwoven fabric suitable for use as a waterproof / breathable material. [Background technology]
[0002] Waterproof and breathable materials, which are both waterproof and breathable, have the function of releasing water vapor generated by sweat from the body to the outside of the clothing and the function of preventing rain from entering the clothing, and are used in sports and outdoor clothing.
[0003] Generally, a waterproof / breathable material is composed of a waterproof / breathable sheet (or a waterproof / breathable layer) and a fabric such as a woven or knitted fabric, but as a method for obtaining a waterproof / breathable material, Patent Document 1 discloses a technology using a wet coating film of polyurethane. Patent Document 2 discloses a technology using a microporous film obtained by stretching and opening holes in a polytetrafluoroethylene film. Furthermore, Patent Documents 3 and 4 disclose technologies using a porous ultrafine fiber nonwoven fabric obtained by electrospinning polyurethane as a waterproof / breathable sheet. [Prior art documents] [Patent documents]
[0004] [Patent Document 1] Japanese Patent Application Publication No. 55-80583 [Patent Document 2] Special Publication No. 51-18991 [Patent Document 3] JP 2008-213391 A [Patent Document 4] JP 2010-84252 A Summary of the Invention [Problem to be solved by the invention]
[0005] However, the method using the wet coating film of Patent Document 1 and the microporous film of Patent Document 2 have low breathability, and in situations where sweating is relatively high, such as sports or hot and humid environments, the speed at which water vapor is released to the outside of the clothing is insufficient, making the clothing prone to becoming stuffy.
[0006] Furthermore, the nonwoven fabrics produced by the electrospinning methods of Patent Documents 3 and 4 have breathability, but due to the manufacturing process, the strength of the fibers constituting the nonwoven fabric is low, and there is a problem that the strength of the nonwoven fabric, particularly the interlayer peel strength, is low.
[0007] Furthermore, in recent years, there has been a demand for waterproof and breathable materials to be made into a mono-material from the viewpoint of ease of recycling, but waterproof and breathable materials are usually constructed by laminating polyester or polyamide fabric (surface, lining, etc.) and a waterproof and breathable sheet. In order to achieve mono-materialization, the waterproof and breathable sheet needs to be made from the same polyester or polyamide as the fabric, but because polyester and polyamide are difficult to dissolve in general-purpose solvents, it has been difficult to industrially produce waterproof and breathable nonwoven fabrics of polyester or polyamide using the electrospinning method.
[0008] For the above reasons, it has been impossible to obtain a waterproof and moisture-permeable polyester or polyamide material having breathability using conventional techniques. [Means for solving the problem]
[0009] The above object is achieved by the following means: (1) A nonwoven fabric composed primarily of polyester or polyamide fibers, having a maximum pore size of 4 μm or less, a ratio of the maximum pore size to the average pore size (maximum pore size / average pore size) of 4.0 or less, and a maximum frequency of 30% or more in the pore size distribution, and containing a water repellent agent. (2) A nonwoven fabric according to (1) above, which is composed of at least two or more kinds of polyester fibers or polyamide fibers having different fiber diameters, characterized in that the variation in fiber diameters of fibers having a diameter of 600 nm or less contained in the nonwoven fabric is 0.1% or more and 20.0% or less, and the fiber diameter ratio (R / r) of the fiber having the maximum fiber diameter (fiber diameter R) to the fiber having the minimum fiber diameter (fiber diameter r) is 5≦R / r≦100. (3) The nonwoven fabric according to (1) or (2) above, characterized in that it has at least two melting points, the lowest melting point of which is 130° C. or higher. (4) Water resistance is 1000mmH2O or more, and moisture permeability is 30000g / m 2 - 24hr or more, breathability is 1.5cm 3 / cm 2 The nonwoven fabric according to (1) or (2) above, wherein the linearity is .s or more. (5) A waterproof and moisture-permeable material using the nonwoven fabric according to any one of (1) to (4) above. (6) Clothing characterized by using the waterproof and breathable material described in (5) above. Effect of the Invention
[0010] Since the nonwoven fabric of the present invention has the above-mentioned configuration, it is possible to provide a waterproof and moisture-permeable material that is easily recycled and has high levels of waterproofness, moisture permeability, breathability, and strength. [Brief description of the drawings]
[0011] [Figure 1] These are examples of pore size distributions of nonwoven fabrics, where (a) is the pore size distribution of a nonwoven fabric in which microspaces exist uniformly (nonwoven fabric of the present invention), and (b) is the pore size distribution when microspaces are formed nonuniformly. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0012] The nonwoven fabric of the present invention is mainly composed of polyester fibers or polyamide fibers, and therefore has excellent recyclability from the viewpoint of chemical recycling.
[0013] Examples of the polyester in the present invention include polyethylene terephthalate, polytrimethylene terephthalate, polybutylene terephthalate, polyethylene naphthalate, and copolymer polyesters thereof.
[0014] The copolymer polyester herein is obtained by copolymerizing the following components, with terephthalic acid as the main dicarboxylic acid component and ethylene glycol as the diol component.
[0015] Preferred copolymerization components include one or more copolymerization components selected from aliphatic dicarboxylic acids such as adipic acid and sebacic acid, aromatic dicarboxylic acids such as phthalic acid, isophthalic acid, diphenyldicarboxylic acid and 5-sodium sulfoisophthalic acid, oxyacids such as oxybenzoic acid, and / or glycols such as diethylene glycol, propylene glycol and polyethylene glycol, EO adducts of bisphenol A (BPA-EO), and the like.
[0016] The polyamide in the present invention may be, for example, polyamides such as poly-ε-capramide (nylon 6), polyhexamethylene adipamide (nylon 66), and copolymer polyamides thereof.
[0017] In the present invention, the term "mainly composed of" means that the fibers constituting the nonwoven fabric account for more than 50% by weight of the fibers. In the present invention, from the viewpoint of chemical recycling and the like, it is preferable that the polyester fibers or polyamide fibers account for 70% or more by weight, more preferably 80% or more, even more preferably 90% or more, even more preferably 95% or more, and most preferably 100%.
[0018] The nonwoven fabric of the present invention is intended to achieve a high degree of waterproofness and the three opposing properties of moisture permeability and air permeability, by virtue of homogeneous microspaces in which defective pores are controlled to be small, and has the following requirements: a maximum pore size of 4 μm or less, a ratio of the maximum pore size to the average pore size of 4.0 or less, and a maximum frequency in the pore size distribution of 30% or more.
[0019] The pore size here refers to a value calculated by the bubble point method. For example, the porous material automatic pore measurement system Perm-Porometer (manufactured by PMI) can be used as the bubble point method. In the measurement by this Perm-Porometer, the nonwoven fabric is immersed in a liquid with a known surface tension value, and gas pressure is increased while being supplied from the upper side of the nonwoven fabric, and the pore size is measured from the relationship between this pressure and the liquid surface tension on the surface of the wet nonwoven fabric. The obtained bubble point pore size is the maximum pore size, and the mean flow pore size is the average pore size. The pore size frequency is expressed as % by converting the obtained value into a percentage.
[0020] The maximum pore size in the present invention is the largest diameter among the through holes formed in the nonwoven fabric, and is an index representing the size of defective holes in the nonwoven fabric. The smaller the maximum pore size, the more the water pressure resistance can be improved, so the maximum pore size is more preferably 3 μm or less, and most preferably 2 μm or less. On the other hand, if the maximum pore size is too small, the breathability is significantly reduced, so the lower limit of the maximum pore size is preferably 0.5 μm or more, more preferably 0.7 μm or more, and most preferably 0.9 μm or more.
[0021] The average pore size in the present invention is the average size of the diameter of the through holes formed in the nonwoven fabric, and is an index representing the denseness within the nonwoven fabric. The smaller the average pore size, the denser the microspaces that can be formed, so the average pore size is preferably 2.0 μm or less, more preferably 1.5 μm or less, and most preferably 1.0 μm or less. On the other hand, if the average pore size is too small, the breathability is significantly reduced, so the average pore size is preferably 0.3 μm or more, more preferably 0.5 μm or more, and most preferably 0.7 μm or more.
[0022] The ratio of maximum pore size to average pore size (maximum pore size / average pore size) is the ratio of the maximum size to the average size of the through holes formed in the nonwoven fabric, and indicates the narrowness of the base of the pore size distribution. The smaller the ratio of maximum pore size to average pore size (maximum pore size / average pore size), the more likely it is that water pressure resistance and breathability can be achieved at the same time, so the ratio is more preferably 3.0 or less, and most preferably 2.0 or less. On the other hand, the technical lower limit can be 1.2, for example.
[0023] In the present invention, the maximum frequency of the pore size distribution is an index showing the homogeneity of the microspaces in the nonwoven fabric. The higher the maximum frequency of the pore size distribution, the more homogeneous the microspaces can be formed, and therefore, it is more preferable that the maximum frequency is 35% or more.
[0024] In other words, the smaller the maximum pore size, the smaller the ratio of the maximum pore size to the average pore size (maximum pore size / average pore size), and the higher the maximum frequency, the smaller the defective pores are controlled and the more homogeneous the microspace of the nonwoven fabric is.
[0025] The nonwoven fabric of the present invention contains a water repellent agent. The nonwoven fabric of the present invention is mainly composed of polyester fibers or polyamide fibers, and therefore, the nonwoven fabric can only exhibit sufficient water resistance by containing a water repellent agent.
[0026] The water repellent in the present invention may be any known water repellent such as a fluorine-based, hydrocarbon-based, silicone-based, etc. The water repellent treatment for imparting the water repellent is preferably carried out by a padding method or a kiss roller method.
[0027] The nonwoven fabric of the present invention is a nonwoven fabric composed of at least two or more types of polyester fibers having different fiber diameters or at least two or more types of polyamide fibers having different fiber diameters, and it is preferable that the variation in fiber diameters of fibers having a diameter of 600 nm or less contained in the nonwoven fabric is 0.1% or more and 20.0% or less, and that the fiber diameter ratio (R / r) of the fiber with the maximum fiber diameter (fiber diameter R) to the fiber with the minimum fiber diameter (fiber diameter r) is 5≦R / r≦100.
[0028] In the present invention, at least two kinds of polyester fibers or polyamide fibers having different fiber diameters refer to a state in which the fibers observed on the surface of the nonwoven fabric have two or more fiber diameter distributions (peaks) when the fibers are graphed with the horizontal axis representing fiber diameter and the vertical axis representing number of fibers. Here, a group of fibers having fiber diameters within each distribution range is defined as one type, and the existence of two or more such fiber diameter distributions means that the fiber is composed of two or more types of fibers in the present invention. The distribution width of the fiber diameters means ±30% of the peak value with the greatest number of fibers present in each fiber diameter distribution. However, when the distribution widths overlap despite the peak values being clearly different, the fiber groups may be distinguished by using a distribution width within a range of ±10% of the peak value. In order to more effectively form a homogeneous microspace with small defective holes as the object of the present invention, it is preferable that the fiber diameter distribution is discontinuous and forms an independent distribution.
[0029] Furthermore, the smaller the variation in the fiber diameter of fibers of 600 nm or less in the nonwoven fabric (hereinafter sometimes referred to as fiber diameter (U600)), the more homogeneous the microspace of the nonwoven fabric can be. The variation in fiber diameter (U600) is more preferably 15.0% or less, even more preferably 10.0% or less, and most preferably 8.0% or less. Meanwhile, the lower limit of the variation in fiber diameter (U600) is preferably as small as possible, but the technical lower limit is 0.1%.
[0030] The fiber diameter (U600) in the present invention is determined as follows. That is, using a scanning electron microscope (SEM), an image is taken at a magnification where 150 to 3000 fibers can be observed on the surface of the nonwoven fabric, and 50 fibers having a width of 600 nm or less are randomly selected from the taken image, and the width in the direction perpendicular to the fiber axis is measured in μm units to two decimal places. The above operation is performed in the same manner for 10 images, and the number average of the evaluation results of the 10 images is rounded off to one decimal place to determine the fiber diameter (U600).
[0031] The variation of fiber diameter (U600) in the present invention is a value calculated as follows: fiber diameter (U600) CV (%) = (standard deviation of fiber diameter / average of island component diameter) × 100 (%). The standard deviation and average of fiber diameter (U600) were determined using the results measured by the above-mentioned method, and values were rounded off to one decimal place to the nearest whole number.
[0032] In the nonwoven fabric of the present invention, the fiber with the largest fiber diameter (fiber diameter R) serves as the skeleton of the nonwoven fabric, providing mechanical strength and ensuring the handleability and moldability of the nonwoven fabric. On the other hand, the fiber with the smallest fiber diameter (fiber diameter r), i.e., ultrafine fibers with extremely low rigidity, are arranged in a bridge-like manner using fibers other than ultrafine fibers as scaffolds, forming fine spaces. From the above viewpoints, the nonwoven fabric of the present invention is preferably composed of at least two or more types of polyester fibers or polyamide fibers with different fiber diameters.
[0033] In the present invention, in order to effectively exert the roles of the fibers with the fiber diameter R and the fiber diameter r, it is preferable that the fiber diameter ratio (R / r) of the fiber with the maximum fiber diameter (fiber diameter R) to the fiber with the minimum fiber diameter (fiber diameter r) is in the range of 5≦R / r≦100. If the fiber diameter ratio R / r is small, the function of each fiber according to the fiber diameter becomes insufficient. For example, if the fiber diameter R is small, the handling property and shaping processability of the nonwoven fabric may be deteriorated, and if the fiber diameter r is large, the specific ability derived from the ultrafine fibers may not be exerted. Therefore, the lower limit of the fiber diameter ratio R / r is more preferably 7 or more, and most preferably 10 or more. On the other hand, the upper limit of the fiber diameter ratio R / r is more preferably 60 or less, and most preferably 40 or less.
[0034] The nonwoven fabric of the present invention preferably has at least two melting points, the lowest of which is 130° C. or higher. By having the lowest melting point of 130° C. or higher, the nonwoven fabric can be used as clothing that is improved in dimensional stability, moisture permeability, and breathability retention when hot-melt-bonded to the outer and inner fabrics.
[0035] The melting point in the present invention refers to the temperature of the melting peak observed by a differential scanning calorimeter (DSC). Specifically, the nonwoven fabric is dried in a vacuum dryer to a moisture content of 200 ppm or less, about 5 mg of the fabric is weighed, and the temperature is increased from 0°C to 300°C at a rate of 20°C / min to measure the melting point.
[0036] The nonwoven fabric of the present invention has a water pressure resistance of 1000 mmH2O or more and a moisture permeability of 30000 g / m 2 - 24hr or more, breathability is 1.5cm 3 / cm 2 It is preferable that the value is equal to or larger than ·s.
[0037] The water pressure resistance in the present invention refers to a value measured according to a method conforming to JIS L1091-1998 water resistance test (hydrostatic pressure method), in which values of 2000 mmH2O or less are measured using method A (low water pressure method), and values of more than 2000 mmH2O are measured using method B (high water pressure method). The higher the water pressure resistance, the more water can be prevented from penetrating into the garment, so 2000 mmH2O or more is more preferable, and 3000 mmH2O or more is even more preferable.
[0038] The moisture permeability in the present invention refers to a value measured according to the method of JIS L1099-1998 B-1. The higher the moisture permeability, the more likely it is that the sweatiness inside the garment can be suppressed. 2 24hr or more is more preferable, 50,000g / m 2 24 hours or more is even more preferable.
[0039] In the present invention, the breathability refers to a value measured in accordance with JIS L1096-1999 Breathability Method A. The higher the breathability, the more likely it is that the stuffiness inside the garment can be suppressed. 3 / cm 2 ·s or more is preferable, 3.0cm 3 / cm 2 ·s or more is even more preferable.
[0040] The fibers constituting the nonwoven fabric in the present invention are preferably highly oriented. For example, in the case of polyethylene terephthalate fibers, the rigid amorphous amount is preferably 20% or more, more preferably 30% or more, even more preferably 40% or more, and most preferably 50% or more. In addition, for example, in the case of nylon 6 fibers, the rigid amorphous amount is preferably 40% or more, more preferably 50% or more, and most preferably 55% or more. By using highly oriented fibers, the strength of the obtained nonwoven fabric is ensured, and the deterioration of performance during handling during production as well as during continuous wearing or repeated washing can be suppressed. Specifically, the tensile strength index of the nonwoven fabric is preferably 5.0 Nm / g or more. From the viewpoint of a nonwoven fabric having moldability suitable for practical use, the tensile strength index is preferably 30 Nm / g or less. The tensile strength index in the present invention refers to a value measured in accordance with JIS P8113:2006.
[0041] An example of the method for producing the wetlaid nonwoven fabric of the present invention will be described below.
[0042] The nonwoven fabric of the present invention is characterized in that the defective pores are controlled to be small and uniform fine spaces are formed, and it can be either a long fiber type or a short fiber type. In this manufacturing method, any of the spunbond method, melt blow method, dry method, wet method, etc. can be used, and it can be manufactured by combining these as necessary.
[0043] Among the various methods for producing nonwoven fabrics, in order to form homogeneous microspaces with small defective pores, which is a characteristic of the nonwoven fabric of the present invention, a wet method, i.e., a wet papermaking method, is preferably used among these production methods, and this makes it possible to stably produce homogeneous microspaces with small defective pores, which is a characteristic of the present invention.
[0044] The wet papermaking method here refers to a method of producing nonwoven fabric by making a papermaking solution in which short-cut short fibers are dispersed in a medium such as water. For example, binder fibers that bond the short fibers together by heat treatment and ultrafine short fibers that form uniform microspaces with small defective pores are put into water, and after a defibration process or beating process as necessary, the mixture is stirred, and paper is made using the papermaking solution in which various short fibers are uniformly dispersed.
[0045] In the process of preparing the papermaking dope, the dispersibility can be adjusted by the amount of short fibers charged, the amount of aqueous medium, the stirring time, etc., and it is preferable to prepare the dope depending on the dispersion state of various short fibers.
[0046] In order to suppress aggregation of the short fibers introduced into the water and to form homogeneous microspaces with small defective pores, the water may contain a dispersant as required.
[0047] The types of dispersants include natural polymers, synthetic polymers, organic compounds, and inorganic compounds. For example, additives that suppress the aggregation of fibers include cationic compounds, nonionic compounds, and anionic compounds. Among them, when the purpose is to improve the dispersibility, it is preferable to use an anionic compound from the viewpoint of the electric repulsion force in the aqueous medium. In the production of the present invention, the amount of the dispersant added is preferably 0.001 to 10 equivalents to the fibers constituting the nonwoven fabric. If the amount is within this range, the dispersibility of the fibers can be improved without impairing the processability of wet papermaking, and the nonwoven fabric of the present invention can be produced.
[0048] The fibers constituting the nonwoven fabric of the present invention may be fibers produced by a conventionally known spinning method, but from the standpoint of productivity and strength, it is preferable to employ a method utilizing melt spinning.
[0049] When producing fibers by melt spinning, the fibers can be obtained by discharging a polymer having a desired cross-sectional shape using a spinneret or composite spinneret having holes of a desired shape according to the purpose.
[0050] The polymer used in the present invention may contain various additives such as inorganic substances such as titanium oxide, silica, and barium oxide, colorants such as carbon black, dyes, and pigments, flame retardants, fluorescent brighteners, antioxidants, and ultraviolet absorbing agents.
[0051] In the manufacturing method of the nonwoven fabric of the present invention, when wet papermaking is adopted, the various short fibers used in the papermaking solution preferably have a fiber length of 0.3 to 30.0 mm. If the fiber length is within this range, the dispersibility in the papermaking solution is maintained, and good wet papermaking is possible.
[0052] The fiber length referred to here is determined as follows. That is, images of the surface of the nonwoven fabric are taken with a microscope at a magnification that allows observation of 10 to 100 fibers whose full length can be measured. The fiber length of 10 fibers randomly extracted from each of the taken images is measured. The fiber length referred to here is the length of one fiber in the longitudinal direction from a two-dimensionally taken image, measured in mm to three decimal places, and rounded off to one decimal place. The above operation is performed for 10 images taken in the same manner, and the simple number average of the evaluation results of the 10 images is taken as the fiber length.
[0053] The fiber length of the short fibers can be adjusted appropriately depending on the application. Generally, as the fiber length increases, the degree of entanglement between the short fibers increases, and the mechanical properties and the dimensional stability of the nonwoven fabric tend to improve. However, since the short fibers tend to entangle and aggregate during stirring in the papermaking solution, it is advisable to adjust the fiber length according to the specifications of the short fibers to be mixed in the papermaking solution and the expected design.
[0054] The binder fibers and other fibers used in the present invention each strengthen the framework of the nonwoven fabric and aim to stabilize the shape, so it is more preferable that the fiber length is 1.0 to 20.0 mm.
[0055] In the production of the nonwoven fabric of the present invention, it is preferable that ultrafine fibers are mixed into the papermaking dope for the purpose of imparting uniform microscopic spaces to the nonwoven fabric by controlling the number of defective pores to be small.
[0056] In the manufacturing process of the nonwoven fabric of the present invention, in order to obtain a nonwoven fabric having homogeneous microspaces in which the ratio of maximum pore size to average pore size (maximum pore size / average pore size) is 4.0 or less and the maximum frequency of the pore size distribution is 30% or more, it is important to use ultrafine fibers with a fiber diameter variation of 0.1% or more and 20.0% or less.
[0057] As a method for producing these ultrafine fibers, sea-island composite spinning by melt spinning is suitable from the viewpoint of increasing productivity, and it is preferable to use a sea-island composite spinneret from the viewpoint of excellent control of fiber diameter. The sea-island fiber refers to a fiber having a structure in which island components made of a slightly soluble polymer are scattered in a sea component made of a readily soluble polymer.
[0058] In the melt spinning of the sea-island composite fiber, it is necessary that the sea-island composite cross section has stability over time, and it is important to consider the combination of polymers that form the sea-island composite cross section.
[0059] In the present invention, it is desirable to select a combination of polymers such that the melt viscosity ratio (ηB / ηA) of the melt viscosity ηA of polymer A to the melt viscosity ηB of polymer B falls within the range of 0.1 to 5.0.
[0060] The melt viscosity here refers to the melt viscosity that can be measured by a capillary rheometer after reducing the moisture content of chip-like polymer to 200 ppm or less using a vacuum dryer, and means the melt viscosity at the same shear rate at the spinning temperature.
[0061] The easily soluble polymer of the sea-island fiber is selected from polyethylene terephthalate, polytrimethylene terephthalate, polybutylene terephthalate, polyethylene naphthalate, and copolymer polyesters thereof. In particular, from the viewpoint of simplifying the dissolution process of the sea component, the sea component is preferably a copolymer polyester that is easily soluble in aqueous solvents or hot water, and in particular, it is preferable to use a polyester copolymerized with polyethylene glycol and sodium sulfoisophthalic acid alone or in combination from the viewpoints of ease of handling and easy dissolution in low-concentration aqueous solvents.
[0062] Here, "easily soluble" means that, when the poorly soluble polymer is used as a standard in the solvent used for the dissolution treatment, the dissolution rate ratio (easily soluble polymer / poorly soluble polymer) is at least 100. Considering the simplification and time reduction of the dissolution treatment in advanced processing, this dissolution treatment can be completed in a short time, and therefore, ultrafine fibers suitable for the present invention can be obtained without unnecessarily deteriorating the poorly soluble component.
[0063] From the viewpoints of solubility in aqueous solvents and simplification of treatment of waste liquid generated during dissolution, polyesters copolymerized with 3 mol % to 20 mol % of 5-sodium sulfoisophthalic acid and polyesters copolymerized with the above-mentioned 5-sodium sulfoisophthalic acid and 5 to 15 wt % of polyethylene glycol having a weight average molecular weight of 500 to 3,000 are particularly preferred.
[0064] From the above viewpoints, a suitable polymer combination for the sea-island fiber is, for example, a polyester in which 3 mol % to 20 mol % of 5-sodium sulfoisophthalic acid is copolymerized and 5 wt % to 15 wt % of polyethylene glycol having a weight average molecular weight of 500 to 3000 is copolymerized as the sea part, and polyethylene terephthalate, polytrimethylene terephthalate, polybutylene terephthalate, polyethylene naphthalate, or copolymers thereof as the island part.
[0065] The spinning temperature of the sea-island composite fiber is preferably set to a temperature at which the polymers used, mainly those with high melting points or high viscosity, exhibit fluidity, as determined from the above-mentioned viewpoints. The temperature at which the polymer exhibits fluidity varies depending on the polymer properties and its molecular weight, but the melting point of the polymer is a guideline, and it is set to a temperature not higher than the melting point + 60°C. At this temperature, the polymer does not undergo thermal decomposition in the spinning head or spin pack, and the molecular weight reduction is suppressed, allowing the sea-island composite fiber to be produced satisfactorily.
[0066] The melt-extruded yarn is cooled and solidified, and then converged by applying an oil or the like, and taken up by rollers with a specified peripheral speed. The take-up speed is determined based on the discharge rate and the target fiber diameter, and a preferred range for stable production of the sea-island composite fiber is 100m / min to 7000m / min.
[0067] It is important to draw the spun sea-island composite fiber from the viewpoint of improving thermal stability and mechanical properties. The drawing may be performed after the spun multifilament is wound up, or may be performed directly after spinning without winding.
[0068] The sea-island composite fiber is preferably made into a tow of tens to millions of fibers, and cut to the desired fiber length using a cutting machine such as a guillotine cutter, slicer, or cryostat. The fiber length L is preferably cut so that the ratio (L / r) of the fiber length L to the island component diameter (corresponding to the fiber diameter r) is within the range of 3000 to 6000. In this range, when the wetlaid nonwoven sheet is made, the number of contact points between the fibers increases, promoting the formation of a bridge structure, and enhancing the reinforcing effect of the sheet.
[0069] If the ratio (L / r) is too high, partial aggregation may occur in the aqueous medium, resulting in a sheet with impaired homogeneity. Conversely, if the ratio is too small, it may cause falling off during the wet papermaking process, so it is preferable to keep the ratio within the above range.
[0070] The island component diameter here essentially coincides with the fiber diameter of ultrafine fibers and is determined as follows. The sea-island composite fiber is embedded in an embedding agent such as epoxy resin, and an image of the cross section is taken with a transmission electron microscope (TEM) at a magnification where 150 or more island components can be observed. If 150 or more island components are not arranged in one filament, fiber cross sections of several filaments are photographed so that a total of 150 or more island components can be observed. In this case, metal staining can be used to make the contrast of the island components clear. The island component diameter of 150 island components randomly extracted from each image of the fiber cross section is measured. The island component diameter here means the diameter of a perfect circle circumscribing a cross section perpendicular to the fiber axis of the two-dimensionally photographed image. A homogeneous dispersion of ultrafine fibers can be produced by dissolving and removing the sea component from the sea-island fiber obtained as described above.
[0071] That is, to obtain the ultrafine fiber dispersion suitable for the present invention, the sea-island fiber after the cutting process may be immersed in a solvent capable of dissolving the easily soluble component (sea component) to remove the easily soluble component. When the easily soluble component is copolymerized polyethylene terephthalate and polylactic acid in which 5-sodium sulfoisophthalic acid and polyethylene glycol are copolymerized, an alkaline aqueous solution such as an aqueous sodium hydroxide solution may be used. In this case, the bath ratio of the sea-island fiber to the alkaline aqueous solution (weight of the sea-island fiber (g) / weight of the alkaline aqueous solution (g)) is preferably 1 / 10000 to 1 / 5, more preferably 1 / 5000 to 1 / 10. By keeping the ratio within this range, it is possible to prevent the ultrafine fibers from being unnecessarily entangled with each other when the sea component is dissolved. In this case, the alkaline concentration of the alkaline aqueous solution is preferably 0.1 to 5 wt%, more preferably 0.5 to 3 wt%. By setting the temperature within this range, the dissolution of the sea part can be completed in a short time, and a fiber dispersion in which ultrafine fibers are uniformly dispersed can be obtained without unnecessarily deteriorating the island parts. In addition, the temperature of the alkaline aqueous solution is not particularly limited, but by setting it to 50°C or higher, the dissolution of the sea part can be accelerated.
[0072] In the present invention, the easily soluble component (sea component) from the sea-island fiber can be used as it is, or the ultrafine fibers can be separated by filtration, washed with water, freeze-dried, etc., and then dispersed in an aqueous medium again to form a sheet. In addition, considering the advanced processing to be used and the handling at that time, it is possible to adjust the pH of the medium by adding an acid or alkali, or to dilute it with water before use. Note that a dispersant may be contained as necessary to suppress the aggregation of the ultrafine fibers over time or to increase the viscosity of the medium to form a stable sheet. Examples of the dispersant include natural polymers, synthetic polymers, organic compounds, and inorganic compounds. For example, additives that suppress the aggregation of fibers include cationic compounds, nonionic compounds, and anionic compounds. Among them, when the purpose is to improve dispersibility, it is preferable to use an anionic compound from the viewpoint of electrical repulsion in the aqueous medium. The amount of the dispersant added is preferably 0.001 to 10 equivalents relative to the ultrafine fibers, and within this range, the dispersibility of the ultrafine fibers can be ensured without impairing the processability of wet papermaking.
[0073] In addition, in the manufacturing process of the nonwoven fabric of the present invention, in order to obtain a nonwoven fabric having a ratio of maximum pore size to average pore size (maximum pore size / average pore size) of 4.0 or less and an average pore size that is highly compatible with denseness and breathability, the blending ratio of fibers having a fiber diameter of 1 μm or more and 8 μm or less that serve as a scaffold for the ultrafine fibers is important. The ratio (W2 / W1) of the blending weight % (W2) of the scaffold fiber diameter of 1 μm or more and 8 μm or less to the blending weight % (W1) of the ultrafine fibers is preferably 4 or more, more preferably 6 or more, and even more preferably 8 or more. Within this range, the ultrafine fibers do not aggregate with each other, and a structure in which the ultrafine fibers bridge the scaffold fiber diameter of 1 μm or more and 8 μm or less is formed, and appropriate voids can be maintained in the nonwoven fabric.
[0074] The papermaking solution prepared by preparing the above-mentioned various short fibers is diluted to a certain concentration, and then dehydrated on an inclined wire or cylinder to form a nonwoven fabric. Examples of the apparatus used for papermaking include a cylinder papermaking machine, a Fourdrinier papermaking machine, an inclined short wire papermaking machine, or a combination of these. In the papermaking process, in addition to the dispersibility of the fibers in the papermaking solution, the papermaking speed, the amount of fibers, and the amount of aqueous medium are adjusted according to the desired basis weight, and the accumulation of fibers during filtration is controlled. The sheet-like material formed here is subjected to a drying process and a heat treatment process to remove moisture and bond the binder fibers, thereby producing the nonwoven fabric of the present invention. As the drying method, a method using hot air ventilation (air through) or a method of contacting with a hot rotating roll (heated calendar roll, etc.) is preferably adopted from the viewpoint of simultaneously drying the sheet-like material and heat bonding the binder fibers.
[0075] In the manufacturing process of the nonwoven fabric of the present invention, in order to obtain a highly densified nonwoven fabric with a maximum pore size of 4 μm or less, a step of performing calendering using a combination of a pair of flat rolls after drying is important. Since the nonwoven fabric of the present invention has small and uniform microspaces with controlled defective pores before calendering, it is possible to obtain a nonwoven fabric with even smaller defective pores and uniform microspaces after calendering.
[0076] The surface temperature of the roll in the calendering process is preferably 70° C. or higher and 150° C. or lower. By setting the surface temperature of the roll to more preferably 80° C. or higher, and even more preferably 90° C. or higher, the nonwoven fabric can be given the mechanical strength required to suppress the deterioration of performance during continuous wearing or repeated washing. On the other hand, by setting the surface temperature of the roll to more preferably 140° C. or lower, and even more preferably 130° C. or lower, it is possible to suppress the formation of a film due to excessive fusion between fibers, and to obtain a nonwoven fabric in which defective pores are controlled to be small and homogeneous fine spaces are maintained.
[0077] The linear pressure in the calendaring process is preferably 50 N / cm or more and 200 N / cm or less. By setting the linear pressure in the calendaring process to more preferably 70 N / cm or more, and even more preferably 90 N / cm or more, the nonwoven fabric can be given the mechanical strength required to suppress the performance degradation during continuous wearing or repeated washing. On the other hand, by setting the linear pressure in the calendaring process to more preferably 180 N / cm or less, and even more preferably 150 N / cm or less, excessive crushing of the microspaces in the nonwoven fabric can be suppressed, and a nonwoven fabric can be obtained in which defective pores are controlled to be small and homogeneous microspaces are maintained.
[0078] The nonwoven fabric of the present invention, when bonded to a fabric such as a woven or knitted fabric via an adhesive, becomes a waterproof and breathable material that can be preferably used in outdoor wear such as mountain climbing clothes, athletic wear, waterproof and breathable clothing such as gloves and shoes, clothing materials such as glove inserts and boot inserts, and building materials such as wallpaper and roof waterproof sheets.
[0079] Here, the waterproof and moisture-permeable material of the present invention may be formed by laminating a nonwoven fabric mainly made of polyester fibers or polyamide fibers and not containing a water repellent on one side of the nonwoven fabric of the present invention. By laminating a nonwoven fabric mainly made of polyester fibers or polyamide fibers and not containing a water repellent, it is possible to suppress condensation on the surface of the fabric when used as clothing and a large amount of sweat is generated or when used in a tent, etc. As the nonwoven fabric to be laminated, a nonwoven fabric mainly made of polyester fibers or polyamide fibers and not containing a water repellent, having a maximum pore size of 4 μm or less, a ratio of the maximum pore size to the average pore size (maximum pore size / average pore size) of 4.0 or less, and a maximum frequency of the pore size distribution of 30% or more is preferable without impairing the characteristics of the present invention. In addition, by laminating a nonwoven fabric having the above characteristics, it is possible to obtain a waterproof and moisture-permeable material that quickly absorbs moisture, diffuses it into the nonwoven fabric, easily promotes evaporation, and has excellent condensation prevention function.
[0080] The waterproof and moisture-permeable material can be produced by a method in which a woven fabric or a nonwoven fabric is attached to a nonwoven fabric via an adhesive or the like.
[0081] Here, as a method for applying an adhesive to a nonwoven fabric, it is preferable to use a knife coater, a bar coater, a gravure coater or the like to impregnate the nonwoven fabric with the adhesive in a dotted, linear or lattice pattern.
[0082] The fabric material is not particularly limited, but is preferably polyester or nylon, the same as the nonwoven fabric. It may be in any form, such as woven fabric, knitted fabric, or nonwoven fabric. Furthermore, the fabric may be dyed or printed by a known method, or may be subjected to antistatic treatment, water repellency treatment, water absorption treatment, antibacterial and deodorizing treatment, antibacterial treatment, ultraviolet shielding treatment, or the like.
[0083] The waterproof and moisture-permeable clothing can be produced by cutting the waterproof and moisture-permeable material to a required size and integrating the cut pieces by a method such as heat sealing. EXAMPLES
[0084] The nonwoven fabric of the present invention will be specifically described below with reference to examples.
[0085] A. Maximum pore size, average pore size and maximum frequency of pore size distribution The pore size was calculated according to the bubble point method (based on ASTMF-316-86) using a porous material automatic pore measurement system Perm-Porometer (manufactured by PMI). The measurement sample diameter was 25 mm, and Galwick (surface tension: 16 mN / m) was used as the measurement liquid with known surface tension to measure the pore size distribution. The bubble point pore size obtained by automatic calculation was used as the maximum pore size, and the average flow pore size was used as the average pore size, rounded off to the second decimal place to the first decimal place. The pore size frequency was calculated by converting the value obtained by automatic calculation into a percentage and displaying it as a percentage, and rounded off to the second decimal place to the first decimal place to use the value obtained by calculation.
[0086] B. Fiber diameter The surface of the nonwoven fabric is photographed with a scanning electron microscope (SEM) at a magnification where 150 to 3000 fibers can be observed on the surface of the nonwoven fabric, and the width of 50 fibers having a width of 600 nm or less randomly extracted from the photographed image is measured in nm units to the second decimal place. The above operation is performed for 10 images in the same manner, and the number average of the evaluation results of the 10 images is rounded off to the second decimal place to obtain a value to the first decimal place, which is the fiber diameter of 600 nm or less (fiber diameter (U600), r). Similarly, the width of 50 fibers having a width greater than 600 nm in the direction perpendicular to the fiber axis is measured in μm units to the second decimal place. The above operation is performed for 10 images in the same manner, and the number average of the evaluation results of the 10 images is rounded off to the second decimal place to obtain a value to the first decimal place, which is the fiber diameter (R) of fibers greater than 600 nm.
[0087] C. Variation in fiber diameter The results were obtained by observing the fiber diameter in the same manner as described in Section B above. For 50 fibers randomly selected from the image, the width in the direction perpendicular to the fiber axis was measured in nm units to two decimal places. The above procedure was repeated for 10 images in the same manner, and the average value and standard deviation were calculated. From these results, the following formula was used: Variation in island distance (CV%) = (standard deviation / average value) x 100 The variation (CV%) of the distance between island components was calculated based on the above, and the value was rounded off to the first decimal place and used.
[0088] D. Eye The weight of the nonwoven fabric cut into a 250 mm x 250 mm square was measured and the unit area (1 m 2 The weight per unit area was converted into weight per unit area and rounded off to the nearest integer to obtain the basis weight of the nonwoven fabric.
[0089] E. Thickness The thickness of the nonwoven fabric was measured in mm using a dial thickness gauge (TECLOCK SM-114, probe shape 10 mmφ, graduation 0.01 mm, measuring force 2.5 N or less). Measurements were taken at five random locations for one sample of 250 mm x 250 mm in size, and the average was rounded off to two decimal places to determine the thickness of the nonwoven fabric.
[0090] F. Porosity The porosity was determined by rounding off the calculated value from the basis weight and thickness of the nonwoven fabric using the following formula to an integer value. Porosity (%) = 100 - (weight) / (thickness x fiber density) x 100 The fiber density should be the density of the fibers that make up the fiber. In the case of PET, it is 1.38 g / cm 3 It was calculated as:
[0091] G. Melting point After the moisture content of the nonwoven fabric was reduced to 200 ppm or less using a vacuum dryer, approximately 5 mg was weighed out and DSC measurement was performed using a TA Instruments DSC Q2000 model, which was heated from 0°C to 300°C at a heating rate of 20°C / min and then held at 300°C for 5 minutes. The melting point was calculated from the melting peak observed during the heating process.
[0092] H. Water pressure resistance JIS L1092-1998 Water resistance (hydrostatic pressure method) 2000mmH2O or less was measured using Method A (low water pressure method), and over 2000mmH2O was measured using Method B (high water pressure method).
[0093] I. Breathability Measured based on JIS L1099-1998 potassium acetate method (B-1 method), except that the value converted to moisture permeability per 24 hours was used.
[0094] J. Breathability Measurement was performed based on JIS L1096-1999 Air Permeability Method A.
[0095] K. Non-tensile strength Five test pieces measuring 15 mm wide x 50 mm long were taken, and a tensile test was carried out in accordance with JIS P8113:2006 using a tensile tester Tensilon UCT-100 manufactured by Orientec Co., Ltd. to measure the tensile strength index of the nonwoven fabric. This procedure was repeated five times, and the simple average of the results was rounded off to one decimal place to obtain the tensile strength index.
[0096] L. Quality stability when heated Assuming processing using a hot melt adhesive, the nonwoven fabric was heated to 110°C and the change in surface quality was evaluated. The surface quality was checked visually for the presence or absence of wrinkles, and those without wrinkles were rated as having a "good" surface quality.
[0097] M. Water absorption As an alternative property for preventing condensation, the water absorbency of the nonwoven fabric surface was measured by the drop method in accordance with JIS L-1907:2010.
[0098] N.Tactile evaluation After measuring the water absorption time, the wetness of the surface was evaluated by touch as follows.
[0099] Grade 5: Dry texture Level 4: Between Level 3 and Level 5 Grade 3: No moisture on the surface, but feels wet to the touch Level 2: Between Level 1 and Level 3 Grade 1: There is moisture on the surface and it feels wet to the touch. Example 1 The island component was polyethylene terephthalate (PET, melt viscosity 160 Pa s), the sea component was polyethylene terephthalate copolymerized with 8.0 mol% 5-sodium sulfoisophthalic acid and 10 wt% polyethylene glycol with a molecular weight of 1000 (copolymerized PET, melt viscosity 121 Pa s), and the sea / island composite ratio was 50 / 50. The yarn was cooled and solidified, and then oil was added and wound up at a spinning speed of 1000 m / min to obtain an undrawn yarn (total discharge rate: 40 g / min). The undrawn yarn was then drawn 3.4 times between rollers heated to 85°C and 130°C (drawing speed 800 m / min) to obtain a sea-island fiber.
[0100] The mechanical properties of this sea-island fiber are sufficient for cutting, with a strength of 2.4 cN / dtex and an elongation of 36%, and the fiber was cut to a fiber length of 0.6 mm.
[0101] The sea-island fiber was treated with 1 wt % sodium hydroxide aqueous solution (bath ratio 1:100) heated to 90℃ to obtain a microfiber dispersion.
[0102] Next, as binder fibers, cut fibers (core component: PET, sheath component: copolymer polyester with a melting point of 164°C) of thermally adhesive core-sheath composite fibers (core component: fiber diameter 10 μm, fiber length 5.0 mm) were mixed at a mixing rate of 30.0 wt%, and cut PET fibers (fiber diameter 4 μm, fiber length 3.0 mm) to serve as a scaffold for the ultrafine fibers were mixed at a mixing rate of 62.5 wt%, and a fiber dispersion was prepared by uniformly mixing and dispersing them with water using a disintegrator.
[0103] The above-mentioned ultrafine fiber dispersion was mixed homogeneously with this fiber dispersion so that the mixing ratio of ultrafine fibers was 7.5% by weight, to prepare a papermaking stock solution. This papermaking stock solution was used to make paper using a square sheet machine (250 mm square) manufactured by Kumagai Riki Kogyo Co., Ltd., and was dried and heat-treated in a rotary dryer with a roller temperature set to 110°C. Then, using a calendar device with a pair of flat rolls, heat treatment was performed under conditions of a temperature of 110°C and a linear pressure of 80 N / cm to obtain a nonwoven fabric. The nonwoven fabric obtained was subjected to a water-repellent treatment with 4% "Asahi Guard" AG710 (manufactured by Asahi Glass Co., Ltd.), and the performance evaluated is shown in Table 1. The nonwoven fabric obtained had a sharp pore size distribution as shown in Figure 1 (a).
[0104] Example 2 A nonwoven fabric was obtained in the same manner as in Example 1, except that the mixing ratio of the cut PET fibers (fiber diameter 4 μm, fiber length 3.0 mm) serving as a scaffold for the ultrafine fibers was changed to 60.0% by weight, and the mixing ratio of the ultrafine fibers was changed to 10.0% by weight. The results are shown in Table 1.
[0105] Example 3 A nonwoven fabric was obtained in the same manner as in Example 1, except that the mixing ratio of the cut PET fibers (fiber diameter 4 μm, fiber length 3.0 mm) serving as a scaffold for the ultrafine fibers was changed to 65.0% by weight, and the mixing ratio of the ultrafine fibers was changed to 5.0% by weight. The results are shown in Table 1.
[0106] Example 4 A nonwoven fabric was obtained in the same manner as in Example 1, except that the total discharge rate during melt spinning was 25.0 g / min, the spinning speed was 1500 m / min, and the draw ratio was changed to 3.0 times. The results are shown in Table 1.
[0107] Example 5 A nonwoven fabric was obtained in the same manner as in Example 1, except that the sheath component in the thermally adhesive core-sheath composite fiber was changed to a copolymer polyester having a melting point of 110° C. The results are shown in Table 1.
[0108] Example 6 A nonwoven fabric was obtained in the same manner as in Example 1, except that the total discharge rate during melt spinning was 20.0 g / min, the spinning speed was 3000 m / min, and the draw ratio was changed to 2.3 times. The results are shown in Table 1.
[0109] Example 7 A sea-island composite fiber was obtained in the same manner as in Example 1, except that nylon 6 (N6, melt viscosity 120 Pa s) was used as the island component, the sea / island component composite ratio was set to 60 / 40, and the obtained undrawn yarn was drawn 3.0 times between rollers heated to 50°C and 90°C.
[0110] The mechanical properties of this sea-island fiber were sufficient for cut processing, with a strength of 3.0 cN / dtex and an elongation of 30%.
[0111] The sea-island fiber was treated with 1 wt % sodium hydroxide aqueous solution (bath ratio 1:100) heated to 90℃ to obtain a microfiber dispersion.
[0112] Next, as binder fibers, cut fibers (core component: N6, sheath component: copolymer nylon with a melting point of 110°C) (core component fiber diameter 10 μm, fiber length 5.0 mm) of thermally adhesive core-sheath composite fibers (core component: N6, sheath component: copolymer nylon with a melting point of 110°C) were mixed at a mixing rate of 30.0 wt%, and cut fibers of nylon 6 (fiber diameter 4 μm, fiber length 3.0 mm) to serve as a scaffold for the ultrafine fibers were mixed at a mixing rate of 62.5 wt%, and a fiber dispersion was prepared by uniformly mixing and dispersing them with water using a disintegrator.
[0113] The above-mentioned ultrafine fiber dispersion was mixed homogeneously with this fiber dispersion so that the ultrafine fiber mixing ratio was 7.5% by weight, to prepare a papermaking stock solution. This papermaking stock solution was used to make paper using a square sheet machine (250 mm square) manufactured by Kumagai Riki Kogyo Co., Ltd., and the paper was dried and heat-treated using a rotary dryer with a roller temperature set to 80°C. The paper was then heat-treated using a calendar device with a pair of flat rolls at a temperature of 80°C and a linear pressure of 80 N / cm to obtain a nonwoven fabric. The nonwoven fabric obtained was treated with 4% "Asahi Guard" AG710 (manufactured by Asahi Glass Co., Ltd.) to impart water repellency, and the evaluation performance was shown in Table 1.
[0114] Example 8 Except for halving the fiber concentration in the papermaking solution, the same procedures as in Example 1 were followed up to the calendaring treatment to obtain two sheets of nonwoven fabric. One of the obtained nonwoven fabrics was subjected to a water-repellent treatment in the same manner as in Example 1.
[0115] A moisture-curing polyurethane hot melt adhesive was heated to 110°C and melted, and applied to the water-repellent treated nonwoven fabric in 0.40 mm x 0.40 mm squares (20 μm deep) at an angle of 45° to the direction of travel of the fabric using a gravure coater equipped with a gravure roll engraved with 40 mesh, and then dried for 1 minute at 20°C. As a result, the adhesive was applied in dots onto the nonwoven fabric, covering 40% of the nonwoven fabric, and the adhesive application amount was 15 g / m. 2 It was.
[0116] Next, the nonwoven fabric that had not been subjected to the water repellent treatment was placed on the adhesive side of the nonwoven fabric coated with the adhesive, and heat-treated at a temperature of 110° C. and a linear pressure of 50 N / cm using a calendaring device with a pair of flat rolls. After that, aging was performed at room temperature for 48 hours to obtain a laminated nonwoven fabric.
[0117] When the water absorbency of the non-water-repellent side of the obtained laminated nonwoven fabric was measured, it was found to be good, taking less than one second. In addition, the water-absorbent side felt dry to the touch, earning a grade of 5 in the texture evaluation.
[0118] Comparative Example 1 Except for not carrying out the calendaring process, a nonwoven fabric was obtained in the same manner as in Example 1. The results are shown in Table 1.
[0119] Comparative Example 2 Except for not carrying out the water-repellent treatment, a nonwoven fabric was obtained in the same manner as in Example 1. The results are shown in Table 1.
[0120] Comparative Example 3 A nonwoven fabric made of polyurethane fibers with an average fiber diameter of 300 nm was produced by electrospinning (solution method, solvent: dimethylformamide) and aged for 48 hours in a room at 40°C. After water repellent treatment with 4% Asahiguard" AG710 (manufactured by Asahi Glass Co., Ltd.), the performance evaluated is shown in Table 1. The obtained nonwoven fabric had a broad pore size distribution as shown in Figure 1 (b).
[0121] Comparative Example 4 The same procedure as in Example 8 was carried out, except that the fabric attached to the adhesive side of the nonwoven fabric was a half tricot made of 22 dtex-20 filament polyethylene terephthalate. When the water absorbency of the surface of the resulting laminate that had not been treated for water repellency was measured, it was only 3 seconds, which was a poor result. In addition, when the water-absorbent surface was touched, it felt wet, and the touch evaluation result was grade 3.
[0122] [Table 1] [Industrial Applicability]
[0123] INDUSTRIAL APPLICABILITY The nonwoven fabric of the present invention has uniform microscopic spaces with small and controlled defective pores, and is therefore easily recyclable and has good breathability, and can be used as a waterproof / breathable sheet for clothing.
Claims
1. A nonwoven fabric mainly composed of polyester fibers or polyamide fibers, having a maximum pore size of 4 μm or less, a ratio of the maximum pore size to the average pore size (maximum pore size / average pore size) of 4.0 or less, and a maximum frequency of the pore size distribution of 30% or more, and containing a water repellent agent.
2. 2. The nonwoven fabric according to claim 1, characterized in that the nonwoven fabric is composed of at least two or more types of polyester fibers or polyamide fibers having different fiber diameters, wherein the variation in fiber diameters of fibers having a diameter of 600 nm or less contained in the nonwoven fabric is 0.1% or more and 20.0% or less, and the fiber diameter ratio (R / r) of the fiber having the maximum fiber diameter (fiber diameter R) to the fiber having the minimum fiber diameter (fiber diameter r) is 5≦R / r≦100.
3. 3. The nonwoven fabric according to claim 1, which has at least two melting points, the lowest of which is 130° C. or higher.
4. Water resistance is 1000mmH 2 O or more, and the moisture permeability is 30,000 g / m 2 ・24 hours or more, breathability is 1.5 cm 3 / cm 2 3. The nonwoven fabric according to claim 1, wherein the linear modulus is greater than or equal to s.
5. A waterproof and moisture-permeable material comprising the nonwoven fabric according to claim 1 or 2.
6. Clothing comprising the waterproof and moisture permeable material according to claim 5.
Citation Information
Patent Citations
Kinzokuryukabutsuno sankaho
JP1976018991A
Production of coating cloth
JP1980080583A
Moisture permeable waterproof cloth
JP2008213391A
Waterproof moisture-permeable laminate and waterproof moisture-permeable material using the same
JP2010084252A